(untitled) - Thomsett, Michael C. (Hoboken, N.J., 2006)
Getting Started in Fundamental Analysis provides valuable coverage of: he audited statement; finding financial information online; the process of confirmation; balance sheet and income statement ratios; how the combination of fundamental analysis with technical methods creates a powerful strategy
Keywords: Investment analysis,Stocks,Phân tích đầu tư,Thị trường chứng khoán